ARE THE PROVISIONS OF ALBANIAN CIVIL CODE ENOUGH GOOD IN ORDER TO OFFER A BETTER PROTECTION TO THE PASSENGERS AND THE GOODS? A THEORETICAL AND PRACTICAL VIEW ON THESE PROVISIONS AND OTHER LEGAL ACTS DISCIPLINING THIS FILED - Teliti, Ersida (European Scientific Journal, ESJ, 2015)
Transportation is a process that has been in help to human kind in every time. It has existed in different manners and forms. First of all, it has been a matter of fact than the society set some rules in order to discipline it. From a historical prospect even the first acts of our newborn state have ruled the transport, firstly as a process and a necessity of civil circulation. Then, through years it got the concept of a contract, specifying the parties, their rights and obligation. The transport contract is named under different names and contracts in accordance with the terms of time. The main goal of this article is not only to offer a historic view of this contract, but to sit in to the provisions of actual Civil Code. The transport contract will be analyzed in a critical view, underlying the problems of it. The weak judiciary practice is a key problem of this paper. In order to offer a full view of our legislation, the paper will offer in the last part of it a specific view of all types of transport, regulated under specific Codes. The recommendations are addressed both to the legislator, to the public authorities and to the government.